Efficacy and safety of the oxaliplatin-based chemotherapy in the treatment of advanced primary hepatocellular carcinoma: A meta-analysis of prospective studies. Issue 40 (October 2016) - Liu, Lin; Zheng, Ying-hui; Han, Li; Qin, Shu-Kui
Abstract: Background: Many clinical studies have demonstrated the survival benefits of oxaliplatin-based chemotherapy for advanced hepatocellular carcinoma patients. Therefore, we aim to evaluate the efficacy and safety of oxaliplatin-based chemotherapy in patients with advanced hepatocellular carcinoma by conducting a meta-analysis of prospective studies. Methods: A comprehensive literature search was performed using the PubMed, Cochrane Library, EMBASE, and Web of Science databases from their inception to June 2016. Only prospective studies evaluating oxaliplatin-based chemotherapy in patients with advanced hepatocellular carcinoma were selected. The main outcomes included objective response rate (ORR), progression-free survival (PFS), overall survival (OS), and main adverse events. Results: Ten prospective studies involving 525 patients were included. The pooled ORR, 1-year PFS, and OS were 14.4% (95% confidence interval [ CI ] 9.2–19.6%), 9.3% (95% CI 10–28%), and 35.7% (95% CI 27–44%), respectively, for oxaliplatin-based chemotherapy. The median PFS and OS were 4.7 and 9.4 months, respectively. The incidences of grade 3/4 toxicities of neutropenia, thrombopenia, anemia, neurotoxicity, diarrhea, and nausea/vomiting were 17.2%, 9.2%, 6.0%, 4.8%, 3.1%, and 1.8%, respectively. Subgroup analysis revealed that the pooled ORR was 13.9% (95% CI 6.8–21%) in Asian patients and 12.8% (95% CI 6.8–18.7%) in Western patients. For Asian patients, the median PFS and OS were 4.2 and 9.2 months, and the 1-year PFS and OS were 12.5% and 30.5%, respectively. For Western patients, the median PFS and OS were 4.7 and 9.5 months, and the 1-year PFS and OS were 19.6% and 42.4%, respectively. There were no significant differences in the ORR, 1-year PFS, and OS ( P  > 0.05) between Asian and Western patients. Conclusions: Oxaliplatin-based chemotherapy appears to be effective and safe for the treatment of advanced hepatocellular carcinoma.